Is only one cognitive technique also effective? Results from a randomized controlled trial of two different versions of an internet-based cognitive behavioural intervention for post-traumatic stress disorder in Arabic-speaking countries. Issue 1 (1st January 2021) - Böttche, Maria; Wagner, Birgit; Vöhringer, Max; Heinrich, Manuel; Stein, Jana; Selmo, Pirko; Stammel, Nadine; Knaevelsrud, Christine
ABSTRACT: Background: Internet-based cognitive-behavioural interventions seem to be effective for the treatment of posttraumatic stress disorder (PTSD) in Arabic-speaking countries in the MENA region. However, due to high prevalence rates of trauma-related mental disorders in this region, it is important to scale up existing Internet-based interventions in order to increase the number of clients. Objective: The aim of the study was to examine whether a brief Internet-based intervention with one cognitive technique (TF-short, 6 assignments) results in the same PTSD symptom change and lower dropouts compared to a longer intervention with two cognitive techniques (TF-reg, 10 assignments). Method: A total of 224 Arab participants (67.4% female; M = 25.3 years old) with PTSD were randomly assigned to Internet-based CBT with either a TF-reg protocol ( n  = 110) or a TF-short protocol ( n  = 114). Symptoms of PTSD and secondary outcomes (anxiety, depression, somatic complaints, quality of life) were self-assessed online at baseline and post-treatment. Treatment-associated changes were estimated using multigroup latent difference score models. Results: The overall PTSD score assessed with the PDS decreased by about 15 points in both conditions. The between-group differences (TF-reg vs. TF-short) at post-assessment were non-significant, Δ = 0.29, p = .896, d = 0.02, 95% CI [-0.30, 0.34]. Like the primary outcome, all within-group changes for the secondary outcomes throughout the intervention were statistically significant and all between-group effects were non-significant. Overall, the dropout rates did not differ between the two conditions, χ2 (1/ N  = 175) = 0.83, p = .364. Conclusions: The findings suggest that the shorter condition results in the same symptom change and dropout rate as the longer condition. This highlights the potential of shorter, more scalable Internet-based interventions in socially restricted and (post-)conflict societies. ClinicalTrials.gov ID: NCT01508377 HIGHLIGHTS: There are no differences regarding PTSD symptom change between an I-CBT with one cognitive technique and a version with two cognitive techniques. Results seem to be promising, as they allow CBT to be offered and scaled up in (post)conflict and socially restricted regions.